Environmental sustainability through green HRM: Measuring the perception of university managers - Lashari, Ishfaque Ahmed; Li, Qiyuan; Maitlo, Qamaruddin; Bughio, Faraz Ali; Jhatial, Ashique Ali; Rashidi Syed, Obed (Frontiers in Psychology, 2022)
Environmental sustainability has earned great momentum worldwide especially United Nations, governments and corporations promoted global awareness on environment challenges and management. As these stakeholders struggle hard, academia has actively engaged in ongoing debate to make green-human-resource-management as an independent field of research and teaching. From large body of academic literature, it has been observed that the field is yet in embryonic stage in developing countries especially in Pakistan and there is insufficient knowledge on how universities experience and manage environmental challenges. Hence, this study addressed this backdrop in the literature and measured perception of public and private sector universities managers regarding environmental sustainability. Using a multi-respondent and multi-wave design data were collected from academic heads/supervisors and university faculty in three time intervals. The data found support for all the hypothetical relationships. Study reveals that GHRM practices of public and private universities integrated with environmental sustainability produce positive outcome.